1999
DOI: 10.1038/sj.bjc.6690146
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of the lipophilic thymidylate synthase inhibitor Thymitaq™ (nolatrexed dihydrochloride) given by 10-day oral administration

Abstract: Summary 2-Amino-3,4-dihydro-6-methyl-4-oxo-5-(4-pyridylthio)-quinazoline dihydrochloride (nolatrexed dihydrochloride, Thymitaq, AG337), a specific inhibitor of thymidylate synthase, was developed using protein structure-based drug design. Intravenously administered nolatrexed is active clinically. As oral bioavailability is high (70-100%), nolatrexed was administered orally, 6 hourly for 10 days, at 3-week intervals, and dose escalated from 80 to 572 mg m -2 day -1 in 23 patients. Common toxicity criteria (CTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Accumulation of dUMP occurs as a direct consequence of TS inhibition and also as a result of increased activity of other enzymes, including ribonucleotide reductase (RR) and deoxycytidylate (dCMP) deaminase (Maybaum et al, 1981). A number of studies have indicated that plasma dUrd is an important pharmacodynamic (PD) marker of TS inhibition (Mitchell et al, 1997;de Jonge et al, 2002;Ford et al, 2002;Rees et al, 2003) especially with the use of the TS inhibitors AG337 (Nolatrexed) (Jodrell et al, 1999;Estlin et al, 2001), ZD9331 (de Jonge et al, 2002;Ford et al, 2002;Rees et al, 2003) and ZD1964 (raltitrexed) (Ford et al, 2002;Horton et al, 2005); however, similar studies have not been performed with pemetrexed.…”
mentioning
confidence: 99%
“…Accumulation of dUMP occurs as a direct consequence of TS inhibition and also as a result of increased activity of other enzymes, including ribonucleotide reductase (RR) and deoxycytidylate (dCMP) deaminase (Maybaum et al, 1981). A number of studies have indicated that plasma dUrd is an important pharmacodynamic (PD) marker of TS inhibition (Mitchell et al, 1997;de Jonge et al, 2002;Ford et al, 2002;Rees et al, 2003) especially with the use of the TS inhibitors AG337 (Nolatrexed) (Jodrell et al, 1999;Estlin et al, 2001), ZD9331 (de Jonge et al, 2002;Ford et al, 2002;Rees et al, 2003) and ZD1964 (raltitrexed) (Ford et al, 2002;Horton et al, 2005); however, similar studies have not been performed with pemetrexed.…”
mentioning
confidence: 99%
“…and 10 day p.o. regimens (Rafi et al, 1995(Rafi et al, , 1998Jodrell et al, 1999;Hughes et al, 2000). The 5 day i.v.…”
Section: Cancer Drug Development In the Uk In The Academic Sector Theunclassified
“…The changing face of chemotherapy in colorectal cancer (Hughes et al, 1999;Jodrell et al, 1999), and phase II studies investigating this agent in a number of solid tumours including colorectal cancer are underway.…”
Section: Reviewmentioning
confidence: 99%